Mechanisms of Arrhythmogenicity of Hypertrophic Cardiomyopathy-Associated Troponin T (TNNT2) Variant I79N - Shafaattalab, Sanam; Li, Alison Y; Gunawan, Marvin G; Kim, BaRun; Jayousi, Farah; Maaref, Yasaman; Song, Zhen; Weiss, James N; Solaro, R. John; Qu, Zhilin; Tibbits, Glen F (Frontiers in Cell and Developmental Biology, 2021)
Hypertrophy cardiomyopathy (HCM) is the most common heritable cardiovascular disease and often results in cardiac remodeling and an increased incidence of sudden cardiac arrest (SCA). HCM causing variants of TNNT2 (cardiac troponin T -TnT) are linked to increased risk of ventricular arrhythmogenesis and sudden death despite causing little to no cardiac hypertrophy and thus a more detailed understanding is critical. In this study, a TNNT2 variant, I79N, was generated in human cardiac reconstituted thin filaments to investigate the effect of the mutation on myofilament Ca2+ sensitivity and Ca2+ dissociation rate. The I79N mutation significantly increased myofilament Ca2+ sensitivity and decreased the Ca2+ off-rate constant (koff). To investigate further, a heterozygous I79N+/- TNNT2 mutation was introduced into human induced pluripotent stem cell- using CRISPR/Cas9 and subsequently differentiated into ventricular cardiomyocytes (hiPSC-CMs). Arrhythmogenesis was investigated by measuring voltage (Vm)and cytosolic Ca2+ transients over a range of stimulation frequencies. An increasing stimulation frequency was applied to the cells, from 55 to 75 bpm. The results of this protocol showed that the TnT-I79N cells had reduced intracellular Ca2+ transients due to the enhanced cytosolic Ca2+ buffering. These changes in Ca2+ handling resulted in beat-to-beat instability and triangulation of the cardiac action potential, which are predictors of arrhythmia risk. While WT hiPSC-CMs were accurately entrained to frequencies of at least 150 bpm, the I79N hiPSC-CMs demonstrated clear patterns of alternans for both Vm and Ca2+ transients at frequencies >75 bpm. Lastly, a transcriptomic analysis was conducted on WT vs. I79N+/- TNNT2 hiPSC-CMs using a custom NanoString codeset. The results showed a significant upregulation of NPPA (atrial natriuretic peptide), NPPB (brain natriuretic peptide), Notch signaling pathway components, and other ECM remodeling components in I79N+/- vs. the isogenic control. This significant shift demonstrates that this missense in the cTnT transcript likely causes a biophysical trigger which initiates this significant alteration in the transcriptome. This TnT-I79N hiPSC-CM model not only reproduces key cellular features of HCM-linked mutations but also suggests that this TnT mutation causes uncharted pro-arrhythmic changes to the human action potential and gene expression.